ANALISIS PERBANDINGAN ANTARA PENDANAAN HUTANG JANGKA PANJANG DENGAN LEASING DALAM PENGADAAN AKTIVA TETAP (Studi Kasus pada PT. Tiga Pilar Sejahtera, Tbk dan PT. Prima Alloy Steel Universal, Tbk) - Indah Rafika; Mohammad Amin; Anik Malikah (Universitas Islam Malang, 2018)
ABSTRACTThis research was conducted with the aim of: 1) To find out the value ofcosts that must be incurred by the company in obtaining fixed assets, if using theleasing approach. 2) To determine the value of costs that must be incurred by thecompany in obtaining fixed assets, if using a long-term debt approach. 3) To findout the comparison between leasing funding and long-term debt in theprocurement of fixed assets for companies by comparing the present value cashoutflow of long-term debt and leasing.In this study the research subject is PT. Tiga Pilar Sejahtera Food Tbk andPT. Prima Alloy Steel Universal, Tbk.The results showed that 1) PT. Tiga Pilar Sejahtera Food Tbk in purchasingproduction machines should use alternative leasing financing rather than longterm debt financing. The procurement of alternative leasing financing machines ischosen because it can save Rp.1,384,381,433. 2) PT. Prima Alloy Steel UniversalTbk in purchasing assets should use alternative long-term debt rather thanfunding leasing financing. Procurement of alternative long-term debt assetschosen because it can save Rp.513,918,134.Keywords: Leasing, Long-Term Debt, Net Present Value (NPV)